Expression-based intrinsic glioma subtypes are prognostic in low-grade gliomas of the EORTC22033-26033 clinical trial. (May 2018) - Gao, Y.; Weenink, B.; van den Bent, M.J.; Erdem-Eraslan, L.; Kros, J.M.; Sillevis Smitt, PAE; Hoang-Xuan, K.; Brandes, A.A.; Vos, M.; Dhermain, F.; Enting, R.; Ryan, G.F.; et al.
Abstract: Introduction: The European Organisation for Research and Treatment of Cancer (EORTC) 22033-26033 clinical trial (NCT00182819) investigated whether initial temozolomide (TMZ) chemotherapy confers survival advantage compared with radiotherapy (RT) in low-grade glioma (LGG) patients. In this study, we performed gene expression profiling on tissues from this trial to identify markers associated with progression-free survival (PFS) and treatment response. Methods: Gene expression profiling, performed on 195 samples, was used to assign tumours to one of six intrinsic glioma subtypes (IGSs; molecularly similar tumours as previously defined using unsupervised expression analysis) and to determine the composition of immune infiltrate. DNA copy number changes were determined using OncoScan arrays. Results: We confirm that IGSs are prognostic in the EORTC22033-26033 clinical trial. Specific genetic changes segregate in distinct IGSs: most samples assigned to IGS-9 have IDH -mutations and 1p19q codeletion, samples assigned to IGS-17 have IDH -mutations without 1p19q codeletion and samples assigned to other intrinsic subtypes often are IDH -wildtype. A trend towards benefit from RT was observed for samples assigned to IGS-9 (hazard ratio [HR] for TMZ is 1.90, P = 0.065) but not for samples assigned to IGS-17 (HR 0.87, P = 0.62). We did not identify genes significantly associated with PFS within intrinsic subtypes, although follow-up time is limited. We also show that LGGs and glioblastomas differ in their immune infiltrate, which suggests that LGGs are less amenable to checkpoint inhibitor–type immune therapies. Gene expression analysis also allows identification of relatively rare subtypes. Indeed, one patient with a pilocytic astrocytoma was identified. Conclusion: IGSs are prognostic for PFS in EORTC22033-26033 clinical trial samples. Highlights: EORTC 22033-26033 examined whether temozolomide (TMZ) improves survival v. radiotherapy (RT) in low-grade glioma patients. This study investigates the transcriptome of samples included in this study. Expression-based intrinsic glioma subtypes (IGSs) are prognostic and genetic changes segregate in distinct IGSs. Our study is important as it provides an independent method for prognostic classification of molecularly similar tumours. We did not observe benefit from RT or TMZ treatment in any of the subtypes.